The Influence of Modeling Techniques and Motivation Learning against Writing Skills of Student News Text of Class VIII SMP Negeri 3 Padang - Novritika Novritika; Harris Effendi Thahar; Irfani Basri (International Conferences on Educational, Social Sciences and Technology)
This study aims to describe the influence of modeling techniques and learning motivation to the news text writing skills of students. This research used quantitative with the 2x2 factorial experimental design. The Sample in this research is 60 students. The instruments used motivation inventory to learn and performance inventory. The results from this study are: First, there are differences among the results of text-writing skills taught by modeling techniques with the results of text-writing skills taught by conventional techniques. Secondly, there are differences as the result of writing skill of news text of students who have high learning motivation with students who have low learning motivation. The result of writing skill of news text of students who have higher learning motivation is higher than students who have low learning motivation. Third, there is no interaction between modeling techniques and learning motivation in influencing the ability to write news text.